2018
DOI: 10.1186/s12881-018-0528-6
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genomic analysis identifies pathogenic variants in maturity-onset diabetes of the young (MODY) patients in South India

Abstract: BackgroundMaturity-onset diabetes of the young (MODY) is an early-onset, autosomal dominant form of non-insulin dependent diabetes. Genetic diagnosis of MODY can transform patient management. Earlier data on the genetic predisposition to MODY have come primarily from familial studies in populations of European origin.MethodsIn this study, we carried out a comprehensive genomic analysis of 289 individuals from India that included 152 clinically diagnosed MODY cases to identify variants in known MODY genes. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 49 publications
0
72
1
3
Order By: Relevance
“…The first two groups of etiologies can be addressed by employing targeted massive parallel sequencing of known MODY genes as a screening tool, and by performing the whole‐exome/‐genome sequencing studies on the remaining patients. In fact, recent studies utilizing the targeted high‐throughput sequencing have shown that, in patients with MODY or with type 2 diabetes, mutations in ABCC8 could be more frequent than those in HNA4A , HNF1B , or INS making this gene as one of the candidates of major MODY genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first two groups of etiologies can be addressed by employing targeted massive parallel sequencing of known MODY genes as a screening tool, and by performing the whole‐exome/‐genome sequencing studies on the remaining patients. In fact, recent studies utilizing the targeted high‐throughput sequencing have shown that, in patients with MODY or with type 2 diabetes, mutations in ABCC8 could be more frequent than those in HNA4A , HNF1B , or INS making this gene as one of the candidates of major MODY genes.…”
Section: Discussionmentioning
confidence: 99%
“…2018) for MODY. Of these, the common four genes, HNF1A , HNF4A , GCK , and HNF1B have accounted for the majority of identified MODY mutations, although, recently, ABCC8 has emerged as a relatively common causative gene in certain populations . Reported breakdowns of mutations vary widely depending on the ethnicity and the route of ascertainment .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, because targeted next‐generation sequencing has become widely available and more comprehensive genetic studies have been performed in patients assumed to have type 1 diabetes, mutations in the ABCC8 have been found to be the causative factor in a significant percentage of patients with MODY. Interestingly, a comprehensive genomic analysis of 152 individuals with clinically diagnosed MODY in South India showed that mutations in the ABCC8 gene were the second most common cause in this population …”
Section: Discussionmentioning
confidence: 99%
“…We also identified MODY 5 in some of our patients [76]. We have recently reported on a comprehensive analysis of all 14 MODY genes and have also reported on what is likely to be a new MODY gene, with a mutation in the NKX6-1 gene, located on chromosome 7 [77]. …”
Section: Monogenic Diabetes: the Field Where Precision Diabetes Has Amentioning
confidence: 98%